Analisis Laporan Keuangan PT FKS Food Sejahtera Tbk: Analysis of Financial Statements of PT FKS Food Sejahtera Tbk - Nur Ulinnuha; Ni Nyoman Sari Ayu; Sri Hermuningsih (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study is motivated by the importance of periodically monitoring the financial health of food manufacturing companies to maintain market stability amid economic fluctuations. The objective of this study is to conduct a comprehensive evaluation of the financial performance of PT FKS Food Sejahtera Tbk through a comparative analysis of the 2024–2025 period. The research method used is quantitative descriptive with financial ratio analysis techniques covering liquidity, activity, solvency, and profitability. The analysis results indicate a significant improvement in the strategic profitability parameters, where net profit grew by 28.28%, driven by operational cost efficiency strategies, as well as a strengthened capital structure with a decrease in the Debt to Equity Ratio (DER) to 0.83 times. However, fundamental liquidity indicators faced pressure, marked by a decline in the Current Ratio to 0.81 times and an extension of the operating cycle to 81 days due to a slowdown in accounts receivable collection. The study’s conclusion emphasizes that while the company demonstrated highly satisfactory profit growth performance, the effectiveness of working capital management needs to be improved. The implications of this study provide strategic recommendations for management to accelerate the cash conversion cycle to mitigate the risk of short-term liquidity deficits in the future.